A relação risco-retorno e o paradoxo de Bowman: uma investigação em empresas brasileiras - Marcos Villela Vieira (2012)
The premise that risk and return have a positive relation to each other represents one of the basic postulates of financial theory, underlying financing and investment strategies used by companies with the purpose of obtaining higher rates of return on the capital invested by company owners. This work studies this association, through a set of financial risk indicators analyzed jointly with the Return On Equity (ROE) rate, with the purpose of: a) validating the premise of a positive association between risk and Return On Equity; b) validating financial leverage strategy as a way of increasing the ROE rate; and c) identification of outstandingfinancial characteristics ofthe best performance companies. The approach used was based on the studies by Bowman (1980), which identified the phenomenon called the Bowman paradox", related to the absence of a positive association between risk and return, within anexpressive number of companies being traded in American stock exchanges. The risk variables were selected based on the usual approach of variability of the return measured by the ROE and by financial risk accounting indicators, defined according to the dynamic model,Minsky's categories of financial liagility (1984), and a set of liquidity, indebtedness and cash flow rates regularly used in traditional financial analysis. The database used was made up by 173 companies with stock traded in Bovespa between 2001 and 2010, grouped into 18 main sectors. The data obtained was subject to the calculation of the means, medians, linear regression parameters, ofthe r2 coefficients, and of the value P. ln accordance with Bowmans theory (1980), risk/return matrices were built and association indexes (Al) determined to identify the positive or negative nature of the associations, calculated for the companies withbest perforrnance (winners) and worst performance (losers). The tests were complemented by calculating the relation between the return obtained (ROE) and the risk variable taken into account. The results obtained show that, unlike what is suggested by the theory, a relevantnegative association (measured by the value P) was identified when ROE variance was used as a risk variable, for the whole sample, for losing companies (ROE below the median), and with high risk (variance above the median). A positive association was noted, mainly, in sectors with a low number of components and/or highly regulated. The analysis of financial risk indicators did not reveal a relevant positive association. The best relations between risk and return were obtained, in all the tests, by companies with more conservative risk positions. Therefore, higher financial risks were not followed by better performance, in the form ofhigher Return On Equity rates. Thus, the results of the survey do not allow for financial leveraging to be validated as an attractive option for increasing the Return On Equity.